2021
DOI: 10.3390/s21092988
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Light-Modulator-Based Multichannel Data Transmission by Vortex Beams of Various Orders

Abstract: We report an atmospheric multichannel data transmission system with channel separation by vortex beams of various orders, including half-integer values. For the demultiplexing of the communication channels, a multichannel diffractive optical element (DOE) is proposed, being matched with the used vortex beams. The considered approach may be realized without digital processing of the output images, but only based on the numbers of informative diffraction orders, similar to sorting. The system is implemented base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…For example, Figure 15 shows detecting results for the phase 13-channel filter, matched with integer and half-integer OVs [ 193 ]. Note, DOEs can be employed to recognize not only the singular phase state of structured light beams but also for detection polarization state [ 4 , 5 , 6 , 194 ]. However, MSs are more suitable for these purposes [ 195 , 196 , 197 , 198 , 199 , 200 ].…”
Section: Detection Of Light With Oammentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Figure 15 shows detecting results for the phase 13-channel filter, matched with integer and half-integer OVs [ 193 ]. Note, DOEs can be employed to recognize not only the singular phase state of structured light beams but also for detection polarization state [ 4 , 5 , 6 , 194 ]. However, MSs are more suitable for these purposes [ 195 , 196 , 197 , 198 , 199 , 200 ].…”
Section: Detection Of Light With Oammentioning
confidence: 99%
“… Detecting OVs: ( a ) phase of a 13-channel filter; ( b ) intensity pattern (negative) in the focal plane and correspondence of diffraction orders to OV values; and ( c ) results of detecting of different OVs in the beam with co-axial superposition exp(− i 2φ) + exp(− i φ) (total OAM μ = −0.5) [ 194 ]. …”
Section: Figurementioning
confidence: 99%
“…Multichannel data transmission in free space can be achieved by means of laser beams with different properties [ 1 , 2 ]. The most common approach is the use of vortex beams of various orders [ 3 , 4 , 5 , 6 , 7 ], as well as cylindrical vector beams [ 8 , 9 ]. To multiplex information transmission channels, it is also possible to exploit both phase and polarization degrees of freedom [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was first discovered by Allen et al in 1992 [5], vortex beam has shown great application potential in optical tweezers technology [6], super-resolution imaging [7], space optical communication [8], quantum entanglement [9], and other fields. At present, there are many methods available for generating vortex beams, such as helical phase plates [10], mode conversion [11], and spatial light modulators [12]. However, these conventional methods require the construction of relatively bulky optical systems.…”
Section: Introductionmentioning
confidence: 99%